Life after a pediatric kidney transplant - Julia Fijo; Ana Sánchez-Moreno (Nefrología (English Edition), 2023)
Introduction and objectives: There is currently no doubt that a kidney transplant with good function is the best treatment we can offer a child with severe kidney failure, improving their growth, development and life in general. But there are few works that follow these patients over the years to find out what their life is like as adults, their achievements and if there are any difficulties that may have arisen from their illness. That has been the objective of this work. Material and methods: We have collected the evolution of 287 patients who received at least one kidney transplant in pediatric age, analyzing not only the survival of grafts and recipients but, fundamentally, their current quality of life. Results: Over a 40-year period (1979−2019), 345 kidney transplants were performed in 287 pediatric recipients, with a rate of retransplantation before reaching the age of majority of 16.7%. Survival, both of patients and grafts, has improved remarkably in the last 20 years. The survival of transplanted patients in the period from 1979 to 1996 at 10, 20 and 25 years after the intervention was 83%, 76% and 65% respectively, and 94% and 82% at 10 and 20 years respectively in those transplanted in the period from 1997 to 2019. Graft survival in the period from 1979 to 1996 at 10 and 20 years was 39% and 18%, increasing in the second period to 68% and 34% respectively. Survival of the first living donor graft (LD) at 5 and 10 years was 94% and 89%. Currently 150 of these patients are adults. Of these, 32% have a stable partner and 6.6% have children. The level of training is lower than that of the general population and many of them have other comorbidities. Conclusions: The life expectancy of pediatric patients with kidney failure transplanted during childhood has improved markedly in recent decades, as has graft survival, being better with a living donor. In general, they consider themselves satisfied with their lives, with great acceptance of their illness and limitations, but -analyzing their testimonies- we conclude that they lack social support, both for themselves and their families, to achieve a higher level of education and better quality of life. Resumen: Introducción y objetivos: Actualmente no hay duda de que un trasplante renal con buena función es el mejor tratamiento que podemos ofrecer a un niño con insuficiencia renal severa, mejorando su crecimiento, desarrollo y actividad en general. Pero hay pocos trabajos que sigan a estos pacientes a lo largo de los años para conocer cómo es su vida de adultos, sus logros y si hay dificultades que han podido derivarse de su enfermedad. Ese ha sido el objetivo de este trabajo. Material y métodos: Hemos recogido la evolución de 287 pacientes que recibieron al menos un trasplante renal en edad pediátrica en nuestra unidad, analizando no solo la supervivencia de los injertos y receptores sino, fundamentalmente, su calidad de vida actual. Resultados: En un periodo de 40 años (1979−2019) se realizaron 345 trasplantes renales en 287 receptores pediátricos, con una tasa de retrasplantes antes de cumplir la mayoría de edad del 16,7%. La supervivencia, tanto de los pacientes como de los injertos, ha mejorado notablemente en los últimos 20 años. La supervivencia de los pacientes trasplantados en el periodo de 1979 a 1996 a los 10, 20 y 25 años de la intervención fue del 83%, 76% y 65% respectivamente, y del 94% y 82% a los 10 y 20 años respectivamente en los trasplantados en el periodo de 1997 a 2019. La supervivencia del injerto en el periodo de 1979 a 1996 a los 10 y 20 años fue del 39% y 18%, aumentando en el segundo periodo al 68% y 34% respectivamente. La supervivencia del primer injerto con donante vivo (DV) a los 5 y 10 años fue del 94% y 89%.Actualmente son adultos 150 de estos pacientes. De ellos, 32% tienen pareja estable y 6,6% tienen hijos. El nivel de formación es menor que el de la población general y muchos de ellos tienen otras comorbilidades. Conclusiones: La esperanza de vida de los pacientes pediátricos con insuficiencia renal trasplantados durante la infancia ha mejorado notablemente en las últimas décadas, así como la supervivencia de los injertos, siendo mejor con donante vivo. En general, ellos se consideran satisfechos con su vida, con gran aceptación de su enfermedad y limitaciones, pero -analizando sus testimonios- concluimos que les falta apoyo social, tanto a ellos como a sus familias, para lograr un nivel educativo más alto y mejor calidad de vida.